2021
DOI: 10.1111/jfpp.16214
|View full text |Cite
|
Sign up to set email alerts
|

Use of pitaya peel powder for partial replacement of wheat flour in cookie making: Effects of particle size of pitaya peel powder on the product quality

Abstract: Pitaya peel powder (PPP) samples passed through 595, 420, 210, or 105‐µm sieves were partially replaced with wheat flour in cookie making. The use of 10% PPP in the cookie formulation significantly increased the content of total dietary fiber, betacyanin, and total phenolics, as well as the antioxidant capacity of the product but slightly reduced its protein and starch content. When the sieve aperture for PPP decreased from 595 to 105 µm, the phenolic content of supplemented cookies increased by 19.2%, the DPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(45 citation statements)
references
References 55 publications
7
38
0
Order By: Relevance
“…In contrast, the ash content of PPP forti ed cookies was 83-220% higher than that of the control cookies. It is reported that calcium, potassium, magnesium, zinc and iron are identi ed in pitaya peel [10], and they are important for human nutrition [29]. Enhancement in PPP ratio from 0 to 25% increased total, insoluble and soluble ber contents of the supplemented cookies by 7.1, 7.4 and 6.7 times, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, the ash content of PPP forti ed cookies was 83-220% higher than that of the control cookies. It is reported that calcium, potassium, magnesium, zinc and iron are identi ed in pitaya peel [10], and they are important for human nutrition [29]. Enhancement in PPP ratio from 0 to 25% increased total, insoluble and soluble ber contents of the supplemented cookies by 7.1, 7.4 and 6.7 times, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Five ratios of pitaya peel powder/wheat our of 0 (control), 10, 15, 20 and 25% (w/w) were used in the cookie preparation. The cookie making procedure was performed as described elsewhere [10].…”
Section: Cookie Preparation In the Laboratorymentioning
confidence: 99%
See 3 more Smart Citations